Summary of motor vehicle and pedal cycle conspicuity: part 2 -pedal cycles - Laurence Clift; Dean Southall (2001)
• Do flashing lights improve conspicuity ? If it is found that they do, then suitable performance characteristics must be developed; • Do steady LED’s provide adequate conspicuity ? If it is found that they do, then suitable performance characteristics must be developed; • Do existing and proposed legislation and standards provide adequate conspicuity ? If they do not, then proposed improvements must be developed.; • Do existing and proposed legislation and standards provide adequate front illumination ? If they do not then proposed amendments must be developed.